Measuring Emotion Dysregulation in Children With Attention-Deficit/Hyperactivity Disorder: Revisiting the Factor Structure of the Emotion Regulation Checklist. Issue 2 (March 2022) - Silverman, Melanie R.; Bennett, Randi; Feuerstahler, Leah; Stadterman, Jill; Dick, Anthony Steven; Graziano, Paulo; Roy, Amy Krain
Highlights: Exploratory factor analysis identifies 4 factors of the Emotion Regulation Checklist. Two ERC factors assess reactivity of positive and negative emotions. Two ERC factors assess adaptive and maladaptive social-emotional functioning. This measure structure supports nuanced assessment of emotional difficulties in ADHD. Abstract: Emotion dysregulation (ED) is prevalent among youth with Attention-Deficit/Hyperactivity Disorder (ADHD) and significantly impacts functioning. Nuanced measurement of ED is central to understanding its role in this disorder and informing treatment approaches. The present study examined the factor structure of the Emotion Regulation Checklist (ERC) among children with ADHD with and without Oppositional Defiant Disorder (ODD). Exploratory factor analysis (EFA) conducted in a sample of 328 youth (mean age = 6.08) with ADHD indicated a four-factor solution, comprised of the following factors: Negative Emotion Lability, Positive Emotion Lability, Socially Appropriate Affect, and Socially Incongruent Affect. The Negative and Positive Emotion Lability subscales assess the reactivity of negatively and positively valenced emotions, respectively. The Socially Appropriate and Socially Incongruent Affect subscales provide an assessment of social-emotional functioning. All subscales discriminated between children with ADHD only and ADHD with co-morbid ODD, such that children with ODD had greater emotional lability and social-emotional difficulties. This revised factor structure of the ERC facilitates a uniquely brief, yet multifaceted and specific, assessment of emotional difficulties in children with ADHD that can inform treatment planning and operationalize emotional reactivity and social-emotional functioning in future research efforts.